2014
DOI: 10.1371/journal.pone.0109459
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Long-Term Aspirin Use and F-Fluorodeoxyglucose Uptake in Colorectal Cancer Measured by PET/CT

Abstract: PurposeThe aim of this study was to evaluate the relationship between long-term aspirin use with pretreatment 18 Fluorodeoxyglucose (FDG) uptake of primary lesions of Colorectal cancer (CRC) and evaluate their clinical significance.Materials and MethodsWe enrolled 84 patients with CRC who underwent 18F-FDG PET/CT scanning before surgery between 1st July 2008 and 1st March 2013 and followed up until 1st March 2014. Maximum standardized uptake value (SUVmax) of the primary tumor was measured by 18F-FDG PET/CT. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(46 reference statements)
2
3
0
Order By: Relevance
“…It only suggested that the tumor N stage, TNM stage were independent prognostic factors. This result was consistent with the findings of SUV in colorectal cancer, and the reason for this result might be related to the small number of cases selected [30]. The 2-year disease-free survival rate of aspirin group was higher than that of the control group, suggesting that long-term oral aspirin can improve the disease-free survival of patients with nonsmall cell lung cancer.…”
Section: Discussionsupporting
confidence: 88%
“…It only suggested that the tumor N stage, TNM stage were independent prognostic factors. This result was consistent with the findings of SUV in colorectal cancer, and the reason for this result might be related to the small number of cases selected [30]. The 2-year disease-free survival rate of aspirin group was higher than that of the control group, suggesting that long-term oral aspirin can improve the disease-free survival of patients with nonsmall cell lung cancer.…”
Section: Discussionsupporting
confidence: 88%
“…It has also been reported that 4 mM aspirin down-regulates GLUT1 expression and glucose consumption in hepatoma cells possibly through targeting NF-κB or NF-κB/HIF1α signaling [35], which coincides with our findings. A clinical report also showed that long-term use of aspirin inhibits F-18 fluorodeoxyglucose (FDG) uptake in colorectal cancer lesions [36]. Finally, we found a visible down-regulation of p-p65, indicating that 4 mM aspirin may inhibit activation of p65 subunit of NF-κB.…”
Section: Discussionsupporting
confidence: 66%
“…According to the International Agency for Research on Cancer, 1.2 million novel cases of colorectal cancer were diagnosed worldwide in 2008, accounting for 8% of all cancer-related mortalities (2,3). The incidence of colorectal cancer is highest in developed countries and regions: Due to economic development and rapid urbanization in recent years in China, which has resulted in dietary and lifestyle changes within the population, the colorectal cancer morbidity and mortality rates in China are now higher than the average rates, worldwide (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer operation is an important method for the treatment of colorectal cancer (5). The clinical manifestations of colorectal cancer may appear in the following ways: Altered defecation habits, stomach ache, abdominal masses, gastrointestinal hemorrhage, jaundice and a change in character of the stool.…”
Section: Introductionmentioning
confidence: 99%